Pengaruh Computer Anxiety, Computer Attitude, Dan Computer Self Efficacy, Kondisi Yang Memfasilitasi Pemakai, Dan Faktor Sosial Terhadap Minat Mahasiswa Komputerisasi Akuntansi Menggunakan Software Akuntansi - Fachroh Fiddin Fiddin; Muhammad Arief (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
Today's accounting transformation requires that all processes must be Real-Time and Integrated Reporting, one of which is calculating debit credit and closing the books in the system and minimal use of paper in the transaction documentation process (Paperless). This study is to see the effect of computer anxiety, computer attitude, computer self-efficacy, facilitating conditions, and social factors on student interest in using accounting software in the accounting learning process. This type of research is quantitative research and the data is obtained by distributing questionnaires in which the sample data is accounting students who are taking accurate accounting computer courses., Data analysis was carried out with Regression Analysis, which consisted of validity test, reliability test, normality test, multiple linear regression test. The results showed that computer anxiety and social factors did not affect students' interest in using accounting software in the accounting learning process. Meanwhile, computer attitude, computer self-efficacy, and conditions that facilitate users affect students' interest in using accounting software in the accounting learning process.